2012
DOI: 10.1371/journal.pone.0033069
|View full text |Cite
|
Sign up to set email alerts
|

High-Anxious Individuals Show Increased Chronic Stress Burden, Decreased Protective Immunity, and Increased Cancer Progression in a Mouse Model of Squamous Cell Carcinoma

Abstract: In spite of widespread anecdotal and scientific evidence much remains to be understood about the long-suspected connection between psychological factors and susceptibility to cancer. The skin is the most common site of cancer, accounting for nearly half of all cancers in the US, with approximately 2–3 million cases of non-melanoma cancers occurring each year worldwide. We hypothesized that a high-anxious, stress-prone behavioral phenotype would result in a higher chronic stress burden, lower protective-immunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 111 publications
1
42
0
3
Order By: Relevance
“…Thus, models that are characterized by classifying individuals based on natural differences in neophobic or anxiety-like behaviors may come closer to modeling innate differences in emotional disposition. The present results are consistent with studies in which rodents that are selected for reduced exploratory behavior to novelty (apomorphine-unsusceptible Wistar line) or display increased anxiety-like behavior in an elevated plus maze also grow larger tumors and/or more lung metastases (Teunis et al, 2002; Dhabhar et al, 2012). However, in the former study, tumor onset could not be measured and in the latter, potentially related baseline physiological “traits” were not assessed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, models that are characterized by classifying individuals based on natural differences in neophobic or anxiety-like behaviors may come closer to modeling innate differences in emotional disposition. The present results are consistent with studies in which rodents that are selected for reduced exploratory behavior to novelty (apomorphine-unsusceptible Wistar line) or display increased anxiety-like behavior in an elevated plus maze also grow larger tumors and/or more lung metastases (Teunis et al, 2002; Dhabhar et al, 2012). However, in the former study, tumor onset could not be measured and in the latter, potentially related baseline physiological “traits” were not assessed.…”
Section: Discussionsupporting
confidence: 91%
“…In another neophobic rat model, blunted corticosterone responses earlier in life predict spontaneous mammary tumors (Cavigelli et al, 2006). Finally, mice that are high in anxiety-like behavior using an elevated plus maze exhibit a greater skin tumor burden than those with low anxiety-like behavior (Dhabhar et al, 2012). Although these studies provide categorical links between biobehavioral measures, immune function, and disease progression, the quantitative nature of such relations has not been addressed prospectively.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of studies Kiecolt‐Glaser and colleagues have demonstrated that chronically stressful situations such as those experienced by caregivers can weaken the immune response, significantly diminishing antibody production against influenza and pneumococcal pneumonia vaccines and increasing the chance of latent herpes simplex virus flare ups . Further, in a range of clinical and experimental studies Dhabhar and his collaborators have also shown that chronic and acute stress can trigger both a deleterious and a protective T‐cell response in a wide variety of immune‐related disorders including cancer, allergy and post‐operative recovery . As you will see throughout this review, there is little that is clear cut within this developing field.…”
Section: Anger Laughter Stress and Tai Chi: Emotion And The Immune mentioning
confidence: 99%
“…This indicates that high-stressed children have a low spontaneous activity of Th2, Tr1, and Th17 cells, which suggests a suppressive immune response. Several studies have shown that stress exposure is associated with impaired cell-mediated acquired immunity (20,(34)(35)(36)(37)(38)(39). In 2010, Freier et al (20) showed that Tregs are downregulated during stress and concluded that this might result in an exacerbation of inflammatory conditions such as an autoimmune condition.…”
Section: Discussionmentioning
confidence: 99%